Visceral Adiposity Associates With Malnutrition Risk Determined by Royal Free Hospital-Nutritional Prioritizing Tool in Cirrhosis - Wang, Xiaoyu; Li, Yifan; Sun, Mingyu; Guo, Gaoyue; Yang, Wanting; Hui, Yangyang; Yu, Zihan; Li, Chaoqun; Fan, Xiaofei; Wang, Bangmao; Zhang, Jie; Zhao, Xingliang; et al. (Frontiers in Nutrition, 2021)
Mounting evidence has suggested the clinical significance of body composition abnormalities in the context of cirrhosis. Herein we aimed to investigate the association between visceral adiposity and malnutrition risk in 176 hospitalized cirrhotic patients. The adiposity parameters were obtained by computed tomography (CT): total adipose tissue index (TATI), visceral adipose tissue index (VATI), subcutaneous adipose tissue index (SATI) and visceral to subcutaneous adipose tissue area ratio (VSR). Malnutrition risk was screened using Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT). Visceral adiposity was determined given a higher VSR on the basis of our previously established cutoffs. Multivariate analysis implicated male gender (OR = 2.884, 95% CI: 1.360-6.115, P = 0.006), BMI (OR = 0.879, 95% CI: 0.812-0.951, P = 0.001), albumin (OR = 0.934, 95% CI: 0.882-0.989, P = 0.019) and visceral adiposity (OR = 3.413, 95% CI: 1.344-8.670, P = 0.010) were independent risk factors of malnutrition risk. No significant difference was observed regarding TATI, SATI and VATI among patients with low/moderate and high malnutrition risk. In contrast, the proportion of male patients embracing visceral adiposity was higher in high malnutrition risk group compared with that in low/moderate group (47.27% versus 17.86%, P = 0.009). Moreover, this disparity was of borderline statistical significance in females (19.05% versus 5.88%, P = 0.061). Assessing adipose tissue distribution might potentiate estimation of malnutrition risk in cirrhotics. It is pivotal to recognize visceral adiposity and develop targeted therapeutic strategies.